PEMANFAATAN ELEKTROLISA AIR SEBAGAI ALRENATIF PENGHEMAT BAHAN BAKAR SEPEDA MOTOR HONDA 100 CC - Utomo, Gatut Prijo; Wijaya, Rhony Mukti (MEKANIKA: Jurnal Teknik Mesin, 2015)
The fuel consumption of vehicle increasingly very important, with bigger CC fuel consumption moreincreasing. The continuously fuel consumption will be caused world energy crises indication, Therefore it isnecessary an effort of alternative energy use in order to create good energy balance. In this research tested andcompared between pure gasoline and hydrogen gas-added fuel (HHO) that result in through water electrolyteprocess. From the gas hydrogen (HHO) producer tool testing with vary long variation of electrode, that are : L =60 mm, and L = 80 mm, d = 15 mm with electrode range of 5 mm. Based on testing analysis that pure gasolinewith volume 10 ml in engine circle of 6000 Rpm, produce effective power 4,7 Hp over within 47,3 seconds. Specificfuel consumption (Sfc) as 0,116 kg/hp . h, and thermis efficiency as 48,1%. While fuel with volume 10 ml of hydrogen gas-added fuel (HHO) using electrode L = 60 mm, d = 15 mm with electrode range of 5 mm in enginecircle 6000 Rpm, produce effective power 4,9 Hp over within 66 seconds. Specific fuel consumption (Sfc) as 0,078kg/hp . h, and thermis efficiency as 71,8%. In engine circle and gasoline volume is same and in similar conditionuse electrode L = 80 mm, d = 15 mm with electrode range of 5 mm, resulting in effective power 5,0 Hp over within64 seconds, Specific fuel consumption (Sfc) as 0,079 kg/hp . h, and thermis efficiency as 70,3%. hydrogen gas-addedfuel (HHO) gained from electrolyte result can be increase engine effective power and engine thermis efficiency aswell as fuel consumption (Sfc).Keywords : electrolyte, HHO, fuel, alternative energy